2011
DOI: 10.1149/1.3593001
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Systems for High Withstand Voltage and Durability I. Linear Sulfones for Electric Double-Layer Capacitors

Abstract: This study reports on new electrolyte systems utilizing linear sulfones. The characteristics of linear sulfones have been evaluated with the primary focus on higher withstand voltage. Investigations have been made on eight different types of linear sulfones with relatively low molecular weights. They were subjected to screening with regard to the melting and boiling point, dielectric con-stant, viscosity and the solubility of electrolyte salts. The results of the investigations were that Ethyl isopropyl sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 14 publications
(18 reference statements)
2
72
0
Order By: Relevance
“…As a result, the estimation for the oxidation and reduction durability on the basis of HOMO-LUMO calculation was not fully consistent with the practical measurements derived from the charge-discharge (withstand voltage) test and the LSV evaluation. As mentioned in our previous report, 5 the possible cause of this inconsistency is that the interaction between electrolyte salts and solvents, between the electrolyte salts themselves, and between electrodes and electrolytes in their respective interfaces, cannot be explained by only considering thermodynamics.…”
Section: Factors Affecting the High Withstand Voltage Of 23bc And Ibc-mentioning
confidence: 86%
See 2 more Smart Citations
“…As a result, the estimation for the oxidation and reduction durability on the basis of HOMO-LUMO calculation was not fully consistent with the practical measurements derived from the charge-discharge (withstand voltage) test and the LSV evaluation. As mentioned in our previous report, 5 the possible cause of this inconsistency is that the interaction between electrolyte salts and solvents, between the electrolyte salts themselves, and between electrodes and electrolytes in their respective interfaces, cannot be explained by only considering thermodynamics.…”
Section: Factors Affecting the High Withstand Voltage Of 23bc And Ibc-mentioning
confidence: 86%
“…Evaluations were carried out using the method we proposed in our previous study, 5,18 namely, using the electrochemical impedance spectra (EIS) to evaluate the leakage resistance between the activated carbon electrode and the electrolyte (R l w ) and the capacitance in activated carbon electrode pores (C w ) for the electrolytes (1.0 mol L −1 SBP-BF 4 /2,3-BC, SBP-BF 4 /PC), with regard to the voltage dependence of the electrolyte resistance in activated carbon electrode pores (R s w ). The EIS was performed using a frequency-response analyzer/potentiostat (Solartron; 1260/1286).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One does not need to sacrifice the power capability by using higherwithstand-voltage media such as sulfolane, 13 linear sulfones, 14 and ionic liquids 15 most of them have high viscosity leading to less power than carbonate counterparts. Figure 6 shows the SEM images for the positive electrode for cell A and cell B after cycling 50 times in the voltage range of 03.0 V. For the cell A (without addition), several graphene layers are found exfoliated from the AC particles due to swelling by the gas generation.…”
Section: Nanostructure Of Ruo 2 ·Nh 2 O/kb Compositementioning
confidence: 99%
“…It was proved that SBP-BF 4 had larger solubility and better capacity performance than the other two salts at wide temperature range. [3][4][5][6][7] Xuewen YU et al 1 had confirmed that the withstand voltage of SBP-BF 4 in alkylated carbonates was able to reach as high as 3.2 V. However, the high voltage performance of SBP-BF 4 and PSP-BF 4 in AN was seldom reported, especially applied in commercial large EDLC.…”
Section: Introductionmentioning
confidence: 99%